The Effectiveness of Consumption of Tempeh Nuggets on Weight Gain of Undernourished Toddlers in the Work Area of the Hutabalang Health Center, Central Tapanuli Regency in 2021 - Rumiris Simatupang; Tinawati Nainggolan (Institute of Computer Science (IOCS), 2022)
The nutritional status of children under five is an important health indicator, because children under five are a group that is vulnerable to nutritional health. One type of PMT that fulfills these needs is by giving processed tempeh which is modified into the form of nuggets,it is hoped that toddlers will be interested so that they have the will to consume it.This study aims to determine the effectiveness of tempeh nuggets consumption on weight gain of undernourished children under five in the working area of ​​Hutabalang Health Center Central Tapanuli Regency in 2021. This type of research is a quantitative study with a one group pre-post test approach with a quasi-experimental research design as many as 15 undernourished toddlers. The results of the study the average weight of undernourished toddlers before being given tempeh nuggets was 8,587 and after being given tempeh nuggets for 14 consecutive days the average weight of toddlers became 8,967 with the meaning that there was an increase in toddler's weight although not too significant with an average increase in body weight. undernourished toddlers by 0.38 kg.The results of the statistical paired T test showed that the t value was -4.551 with a P-value of 0.000<0.005,meaning that tempeh nuggets were effective in increasing the weight of undernourished children under five.It is hoped that mothers who have under-fives with malnutrition provide additional food intake in the form of processed tempeh as a side dish or snack with high protein content so that toddlers quickly recover to their normal weight.